Cheddar enzyme modified cheese : influence of protease and lipase on flavour - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Dissertation (M Inst Agrar ( Food Processing))--University of Pretoria, 2008.